Tinjauan Al-Qur’an dan Hadits Tentang Manajemen Waktu (Literature Review) - Aprima, Septi Gia; Arnol, Arnol; Satriadi, Inong (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out the concept of time management in the perspective of the Qur'an and Hadith. This research was carried out using a qualitative approach using the literature review method. Various sources were analyzed, namely the Qur'an and Hadith as the main sources of research data, as well as research results published through various journals on the google scholar website. Data generation is carried out using the keywords "time management", and "time management in Islam. The collected data was analyzed qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of data analysis show that time management is a very important science to learn and apply in daily life, especially related to the use of time for learning. The Qur'an as a holy book that is used as a guideline for Muslims has provided a way to become a lucky person. Respecting time is a demand that must be done by every Muslim. In the Quran and Hadith, we can find many verses and hadiths that show the importance of respecting time. To make good use of our time, we can create a daily schedule, avoid things that hinder productivity, and pray for the ability to appreciate time. Thus, we can become better and productive Muslims.